2020
DOI: 10.1002/job.2439
|View full text |Cite
|
Sign up to set email alerts
|

Beyond demographic identities and motivation to learn: The effect of organizational identification on diversity training outcomes

Abstract: There is a pressing need for better explanations of diversity training effectiveness so that organizations can administer training programs that facilitate positive intergroup interactions. In this paper, we consider the unique predictive effect of organizational identification on diversity training outcomes beyond the effects of the traditional predictors of demographic-based identities and motivation to learn across two samples of employees involved in diversity-related training at their employing organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 56 publications
0
14
0
2
Order By: Relevance
“…Their willingness to offer affective and behavioral support to the organization is lower. Prior researchers have found that low levels of organizational identification have negative effects on individual motivation [54], which is related to absenteeism and organizational citizenship behavior [55,56]. Thus, based on the above reasoning, we propose that organizational identification is negatively associated with CWB.…”
Section: Mediating Effects Of Organizational Identificationmentioning
confidence: 68%
“…Their willingness to offer affective and behavioral support to the organization is lower. Prior researchers have found that low levels of organizational identification have negative effects on individual motivation [54], which is related to absenteeism and organizational citizenship behavior [55,56]. Thus, based on the above reasoning, we propose that organizational identification is negatively associated with CWB.…”
Section: Mediating Effects Of Organizational Identificationmentioning
confidence: 68%
“…In measuring training effectiveness, this paper applies several well-studied metrics that capture the extent to which training achieves its intended objectives (Sitzmann & Weinhardt, 2015), which can include reaction objectives (i.e., how trainees feel about the training program; Kirkpatrick, 1976), learning objectives (i.e., positive changes in trainees' knowledge, attitudes, or skills; Kirkpatrick, 1976), and/or performance objectives (i.e., transfer of learning to the work context; Holton, 1996). In addition, training motivation has been shown to be a key predictor of these training outcomes (Colquitt et al, 2000), and training research often investigates trainees' transfer motivation (i.e., trainee's intentions to exert effort toward using the training information and skills in the workplace; Seyler et al, 1998) and other behavioral intentions (e.g., intentions to report) as motivation-and self-efficacy-related proxies for transfer behaviors (Bingham & Scherer, 2001;Goldberg, 2007;Rawski & Conroy, 2020)…”
Section: Vr Training Methodsmentioning
confidence: 99%
“…If the organization reacts to more negative emotions, the level of the ability to integrate and apply resources is lower, employees’ organizational identification is lower, less interaction and knowledge sharing will take place in the organization and the faster the potential energy cycle decreases in learning resources. Some researchers believe that when employees agree with organizational values, such identification may be significantly related to positive employee behaviors (Rawski and Conroy 2020). Based on the above analysis, we put forward the hypothesis:
Hypothesis 2: Organizational emotional capability is related to organizational learning through the mediation of organizational commitment.
…”
Section: The Mediating Effect Of Organizational Commitmentmentioning
confidence: 99%